The Effect of Human Capital and Total Quality Management on Managerial Performance with the Reward System as A Moderation Variable at PT Pegadaian Regional Office I Medan - Glenn Petrus Hardikusuma; Nicholas Marpaung (Formosa Journal of Applied Sciences, 2023)
This research aims to analyze the influence of human capital and total quality management on managerial performance with the reward system as a moderating variable. The form of research used is quantitative with an associative approach. The population in this study used the Slovin formula with a total of 36 respondents as samples. The data collection technique used a questionnaire. The data analysis methods used are instrument testing, classical assumption testing, moderated regression analysis and hypothesis testing using SPSS. The results of the research conducted show that human capital and total quality management have a partially significant effect on managerial performance at PT Pegadaian Regional Office I Medan.